THE INVESTIGATION OF TAXPAYER COMPLIANCE IN TAX AMNESTY - Diamastuti, Erlina; Hardanti, Kurniasari Novi (AKRUAL: JURNAL AKUNTANSI, 2019)
This study aims to interpret taxpayer behavioUr in the implementation of tax amnesty with qualitative approach. The main data sources are from 8 informants. The informant is a taxpayer both personal and business entity in Surabaya who have implemented the tax amnesty program in phase I and II, which starts in July 2016 until December 2016. The results of this study, first few informants disobedient in taxation liability. Secondly, tax amnesty has not made taxpayer obey yet. Conclusion, Tax Amnesty is not a choice but compulsion.Studi ini menginteprestasi perilaku Wajib Pajak dalam pelaksanaan tax amnesty dengan pendekatan kualitatif. Sumber data utama berasal dari 8 informan. Informan tersebut merupakan wajib pajak baik pribadi maupun badan di Surabaya yang telah melaksanakan program tax amnesty pada tahap I dan II yaitu dimulai pada bulan Juli 2016 sd Desember 2016. Hasil Studi ini, Pertama, sebagian informan tidak patuh dalam kewajiban perpajakannya. Kedua, Tax amnesty belum membuat wajib pajak menjadi patuh. Simpulan, Tax Amnesty bukan sebuah pilihan kepatuhan tapi sebuah keterpaksaan.